Heat Capacity and Thermodynamic Functions of New Cobalt Manganites NdM CoMnO5 (MI = Li, Na, and K) in the Range of 298.15–673 K - Kasenov, B.K.; Turtubaeva, M.O.; Amerkhanova, Sh.K.; Nikolov, R.N.; Kasenova, Sh.B.; Sagintaeva, Zh. I. (Maik Nauka Publishing / Springer SBM, 2017)
Temperature dependences of the heat capacity of cobalt manganites NdM CoMnO5 (MI = Li, Na, and K) are studied by means of dynamic calorimetry in the range of 298.15−673 K. It is found that λ-shaped effects are observed on the curve of cobalt manganites, due probably to second order phase transitions. Based on the experimental data, equations for the temperature dependences of the heat capacity of cobalt manganite are derived with allowance for the temperatures of phase transitions. The values of thermodynamic functions Н°(T)–Н°(298.15), S°(T), and Фхх(T) are calculated.
Keywords: cobalt manganite; dynamic calorimetry; heat capacity; thermodynamic functions